Upaya Pemberdayaan Masyarakat Petani Muda Melalui Program Youth Entrepreneurship and Employment Support Services (YESS): Studi Kasus di Desa Puspo Kabupaten Pasuruan - Imro’atul Fadilla; Rosyidatuzzahro Anisykurlillah (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Indonesia, as an agricultural country, has a large population whose livelihoods are in the agricultural sector. However, the composition of Indonesian farmers by age is mostly over 40 years old compared to young farmers whose percentage is smaller. The decline in the number of young farmers occurs due to a decrease in interest or desire to have jobs in the agricultural sector. The Youth Entrepreneurship and Employment Support Services (YESS) program seeks to create entrepreneurs and improve the competency of the younger generation of professionals in the agricultural sector. The purpose of this study is to analyze the empowerment of young farmers through the Youth Entrepreneurship and Employment Support Services (YESS) program in Puspo Village, Pasuruan Regency. This study uses a qualitative descriptive approach with data collection techniques in the form of observation, interviews, and documentation. The research results in the enabling stage, as an effort to create potential through training, competitive grants, and certified internships in the YESS program, were optimally implemented, able to encourage and motivate communities to develop their opportunities. Then, in the empowering stage, as an effort to strengthen community potential, it was realized through training for agricultural sector management using a modern approach, through capital assistance from competitive grants, and through certified internships for experience and knowledge in agricultural sector management innovation. Then, in the protecting stage, as an effort to protect and support, it was realized through assistance in managing business permits and the existence of a millennial farmer producer cooperative. However, the operationalization of the millennial farmer producer cooperative did not run optimally due to the lack of sustainability and clarity regarding its function as a place to market agricultural products.